The Republican Wreck at Nido del Cuervo (Águilas, Spain): Rediscovering a Roman Lead Ingot-carrying Ship - Lucarini, Carlotta (The international journal of nautical archaeology, 2025)
The Nido del Cuervo site (Águilas, Spain) has traditionally been interpreted as one of just a few Late Republican Roman lead ingot carrying wrecks, due to the exceptional discovery of 15 Roman ingots at the site. Although the remains were never published, the original excavation report indicated a consistent cargo of Dressel 1C and Dressel 28 amphorae and suggested that the ship sank around 60–50 BC. This study involves the review of all the unpublished preserved remains recovered from the site, with the caveat that no section of a ship’s hull has been documented, and challenging the assumption that these amphorae were part of the cargo of a single ship. Much of the materials thought to be Republican are, in fact, Imperial or Late Roman. The reinterpretation of the context suggests that some of the materials may belong to a late 1st-century BC wreck.